Pemetaan Pola Pencemaran Air Tanah Berdasarkan Karakteristik Fisik Di Desa Olele, Kabupaten Bone Bolango - Paladan, Reynhard Batara; Paladan, Rayhand Batara; Nurfaika, Nurfaika; Ninasafitri, Ninasafitri; Zainuri, Ahmad (Universitas Negeri Gorontalo, 2025)
This study maps the groundwater pollution pattern due to seawater intrusion in Olele Village, Bonebolango Regency, Gorontalo. This area has high maritime and ecotourism potential, but increasing tourism activities and population increase the need for clean water and the risk of seawater intrusion. The impact can affect air quality, land productivity, and public health. The study used a qualitative descriptive approach through field surveys, physical measurements of wells, and air quality tests (pH, EC, TDS, salinity), as well as semi-structured interviews. Data analysis was carried out using descriptive statistics, GIS-based spatial mapping, and thematic analysis. The results showed that the dominant TDS value was categorized as